2021
DOI: 10.2174/1389200222666210705122913
|View full text |Cite
|
Sign up to set email alerts
|

ADMET Profiling in Drug Discovery and Development: Perspectives of In Silico, In Vitro and Integrated Approaches

Abstract: : In the drug discovery setting, undesirable ADMET properties of a pharmacophore with good predictive power obtained after a tedious drug discovery and development process may lead to late-stage attrition. The early-stage ADMET profiling has introduced a new dimension to leading development. Although several high-throughput in vitro models are available for ADMET profiling, however, the in silico methods are gaining more importance because of their economic and faster prediction ability without the requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Prediction of ADMET (absorption, distribution, metabolism, excretion, and toxicity) properties (Amin et al, 2021;Daoud et al, 2021;Dwivedi et al, 2021) for all the target compounds was the same as that for compounds 1e, 1f, and 1g, which indicated that modified compounds would be expected to have similar pharmaceutical properties to the original drugs. All the compounds except f-1 and 7-e to 10-e met the requirements of Lipinski's rule of five (their molecular weight ≤500 Da, lipophilicity, and the number of HBD ≤5, and the number of HBA and rotatable bonds ≤10).…”
Section: Admet Predictionmentioning
confidence: 79%
“…Prediction of ADMET (absorption, distribution, metabolism, excretion, and toxicity) properties (Amin et al, 2021;Daoud et al, 2021;Dwivedi et al, 2021) for all the target compounds was the same as that for compounds 1e, 1f, and 1g, which indicated that modified compounds would be expected to have similar pharmaceutical properties to the original drugs. All the compounds except f-1 and 7-e to 10-e met the requirements of Lipinski's rule of five (their molecular weight ≤500 Da, lipophilicity, and the number of HBD ≤5, and the number of HBA and rotatable bonds ≤10).…”
Section: Admet Predictionmentioning
confidence: 79%
“…These products can be chemically reactive and lead to DNA adducts modifications, mutations, and disruption of enzyme reactions. Many current QSAR models, molecular docking tools and ADMET properties prediction tool in silico are available to weigh the toxicity of chemicals (Daoud et al 2021 ). Table 1 shows the comprehensive list of ADMET profiling tools, the parameters one can predict with their link adopted with permission from references (Shin et al 2017 ).…”
Section: Essential Role Of Pbpk Models and Admet Profilers In Health ...mentioning
confidence: 99%
“…Lipophilicity is a valuable parameter of the drug which affects its activity in the human body. The Log P value of the compound indicates the permeability of the drugs to reach the target tissue in the body [39] LogS…”
Section: Logpmentioning
confidence: 99%
“…Our estimated logS value is a unit stripped logarithm (base 10) of the solubility measured in mol/liter. [39] CYP inhibitors…”
Section: Logpmentioning
confidence: 99%